2007
DOI: 10.1161/circulationaha.106.653964
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Incremental Mortality Risk Prediction by Cortisol and Aldosterone in Chronic Heart Failure

Abstract: Background-In patients with systolic heart failure, high levels of circulating aldosterone are associated with an adverse prognosis, and mineralocorticoid receptor blockade improves survival. The prognostic significance of cortisol that may also bind and activate the mineralocorticoid receptor in chronic heart failure is unknown. Methods and Results-Serum levels of cortisol and aldosterone were quantified in a prospective cohort study of 294 consecutive patients with chronic heart failure [48% were in New York… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
158
2
13

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(187 citation statements)
references
References 48 publications
10
158
2
13
Order By: Relevance
“…In the Caerphilly Heart Study, Davey-Smith et al (113) reported a positive association between the plasma cortisol/testosterone ratio and incident vascular disease; cortisol alone was not an independent predictor. In smaller studies, higher plasma cortisol has also been associated with the extent of atheromatous disease quantified by coronary angiography (114), and predicted mortality in patients with heart failure (115). Polymorphisms in the GR gene have recently been associated with cardiovascular event rate in populationbased studies in Rotterdam (SWJ Lamberts, personal communication) and Sydney (116) ( Table 1).…”
Section: Endogenous Glucocorticoidsmentioning
confidence: 98%
“…In the Caerphilly Heart Study, Davey-Smith et al (113) reported a positive association between the plasma cortisol/testosterone ratio and incident vascular disease; cortisol alone was not an independent predictor. In smaller studies, higher plasma cortisol has also been associated with the extent of atheromatous disease quantified by coronary angiography (114), and predicted mortality in patients with heart failure (115). Polymorphisms in the GR gene have recently been associated with cardiovascular event rate in populationbased studies in Rotterdam (SWJ Lamberts, personal communication) and Sydney (116) ( Table 1).…”
Section: Endogenous Glucocorticoidsmentioning
confidence: 98%
“…Aldosterone is also produced within the heart and works directly on heart tissue at the sites where the hormone is produced. 66 Increased levels of aldosterone in the circulation or in heart tissue stimulate excessive production of collagen, which leads to cardiac fibrosis and cardiac remodeling. 66 Further, cortisol may mimic the effects of aldosterone in patients with heart failure because of changes caused by damage to myocardial tissue.…”
Section: Activation Of the Hpa Axismentioning
confidence: 99%
“…66 Increased levels of aldosterone in the circulation or in heart tissue stimulate excessive production of collagen, which leads to cardiac fibrosis and cardiac remodeling. 66 Further, cortisol may mimic the effects of aldosterone in patients with heart failure because of changes caused by damage to myocardial tissue. 66 Elevated serum levels of cortisol and aldosterone are independent predictors of mortality in patients with heart failure.…”
Section: Activation Of the Hpa Axismentioning
confidence: 99%
See 1 more Smart Citation
“…Serum levels of the hormone aldosterone are increased in patients with HF with both reduced and preserved ejection fraction (HFrEF and HFpEF, respectively), and predict mortality risk (Guder et al. 2007; Girerd et al. 2013).…”
Section: Introductionmentioning
confidence: 99%